Churches and COVID-19: Key Trends in Congregational Life Since the Pandemic - Charissa Mikoski (Religions)
The COVID-19 pandemic and the resulting stay-at-home orders disrupted religious life across the United States, forcing congregations to rapidly adapt to unprecedented challenges. While existing research has explored the pandemic’s impact on individual religiosity, this article centers on how congregations were reshaped by the pandemic—sometimes temporarily, sometimes permanently. Drawing on nationally representative survey data from the Exploring the Pandemic Impact on Congregations project and the long-running Faith Communities Today initiative, this article analyzes trends in worship attendance, other forms of commitment to and engagement with congregations, congregational openness to change, and clergy well-being. The findings show that in-person worship attendance continues to decline, while online worship was adopted widely during the pandemic and remains common. Programming, volunteering, and financial giving have rebounded but still fall short of pre-pandemic levels or current needs. Many congregations embraced change early in the pandemic but have since reverted to old routines. Clergy are in relatively good health, yet growing numbers are reconsidering their futures in ministry. These shifts reveal the pandemic’s lasting impact on congregational life and raise critical questions for clergy, lay leaders, and researchers about institutional resilience, innovation, and leadership sustainability. The findings underscore the complex and evolving nature of post-pandemic ministry.